2012
DOI: 10.2337/dc12-0656
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Placebo-Controlled Comparison of Amitriptyline, Duloxetine, and Pregabalin in Patients With Chronic Diabetic Peripheral Neuropathic Pain

Abstract: OBJECTIVEChronic diabetic peripheral neuropathic pain (DPNP) is difficult to treat, with treatment regimens often inadequate at controlling pain and limited by side effects and drug tolerance. Secondary parameters, such as quality of sleep and mood, may also be important for successful DPNP management. The objectives of this study were to compare the analgesic efficacy of pregabalin, amitriptyline, and duloxetine, and their effect on polysomnographic sleep, daytime functioning, and quality of life in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(150 citation statements)
references
References 34 publications
4
133
0
3
Order By: Relevance
“…Interestingly, a paper comparing the efficacy of neuralgia medications for diabetic neuropathy among patients randomized and placebo-controlled to receive amitriptyline, duloxetine, or pregabalin also found that no one medication emerged as superior (Boyle et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a paper comparing the efficacy of neuralgia medications for diabetic neuropathy among patients randomized and placebo-controlled to receive amitriptyline, duloxetine, or pregabalin also found that no one medication emerged as superior (Boyle et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological treatments, with exception to those targeted to the glycemic control, are symptomatic, not focused on the pathophysiological mechanisms, limited by side effects [3,121] and by the development of tolerance [121] . A wide variety of drugs, used alone or in combination, has been shown to significantly reduce neuropathic pain compared with placebo in randomized controlled trials, but pain relief remains inadequate for most patients [122] .…”
Section: Treatment Of Dnpmentioning
confidence: 99%
“…efficacy was observed between amitriptyline, duloxetine, and pregabalin. There were no significant safety results; however, in the pregabalin group there were a significantly higher number of adverse events (26). In a clinical trial, Tanenberg et al investigated three groups of patients with DPNP: duloxetine, pregabalin, and duloxetine plus gabapentin recipient groups.…”
Section: Discussionmentioning
confidence: 99%